1996
DOI: 10.1016/0042-6989(96)00090-9
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Depth Constancy Depends on the Subject's Task

Abstract: Under identical viewing conditions, observers made two types of judgement about the shape of stereoscopically defined surfaces: one required an estimate of viewing distance for correct performance (e.g. setting the depth of a hemi-cylinder to equal its half-height or a dihedral angle to 90 deg), the other did not (matching the depth of, for example, sinusoidal corrugations or hemi-cylinders presented at two distances). Depth constancy for the two types of task was about 75% and 100%, respectively. We argue tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
117
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 23 publications
14
117
5
Order By: Relevance
“…As expected, perceived depth was greater in the 20¢ of arc than in the 10¢ of arc disparity condition, and, furthermore, perceived depth for each disparity condition increased as a function of viewing distance. The latter result is consistent with those previously reported in the literature relevant to stereoscopic depth constancy (e.g., Glennerster, Rogers, & Bradshaw, 1996;Ono & Comerford;1977;Patterson et al, 1995;Ritter, 1977Ritter, , 1979Shimono, Nakamizo, & Tsuchida, 1990). The depth data were submitted to a two-way repeated measures (4 disparity 3 3 viewing distance) ANOVA.…”
Section: Methodssupporting
confidence: 82%
“…As expected, perceived depth was greater in the 20¢ of arc than in the 10¢ of arc disparity condition, and, furthermore, perceived depth for each disparity condition increased as a function of viewing distance. The latter result is consistent with those previously reported in the literature relevant to stereoscopic depth constancy (e.g., Glennerster, Rogers, & Bradshaw, 1996;Ono & Comerford;1977;Patterson et al, 1995;Ritter, 1977Ritter, , 1979Shimono, Nakamizo, & Tsuchida, 1990). The depth data were submitted to a two-way repeated measures (4 disparity 3 3 viewing distance) ANOVA.…”
Section: Methodssupporting
confidence: 82%
“…In order to perceive the values d 1 and d 2 , the observer must have information about the egocentric distance of the object (D) to scale the relative depth information and size specified at the retina (Glennerster, Rogers & Bradshaw, 1996;Landy et al, 1995;Kaufman et al, 2006). If cues to egocentric distance are available, the 3-D shape, scale and absolute depth values can all, in principle, be derived ( Figure 4B).…”
Section: An Alternative Theory Of Stereopsismentioning
confidence: 99%
“…There have been several propositions that the perception of 3-D space consists of multiple distinct or dissociated representations; related to stages of information processing, or tied to specific adaptive roles. For example, some authors have suggested that depth processing proceeds in a constructive fashion, from the initial detection of depth order, to the derivation of quantitative relative depth relations, to the final derivation of absolute depth values (Glennerster, Rogers & Bradshaw, 1996). They proposed that different visual functions may have access to different stages of this processing.…”
Section: Relation To Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection starts even earlier if one considers the movements we make to obtain the information. Separate independent processing for different judgments can result in substantial conf1icts between them (Abrams & Landgraf 1990;Glennerster et al 1996;Mack et al 1985). Nevertheless, the separation seems be so complete that we even fail to notice conflicts between attributes when the conflicts themselves could give us valuable additional information (Brenner & Damme 1999;Brenner & Landy 1999).…”
Section: We Are Better Off Without Perfect Perceptionmentioning
confidence: 99%